Technology-related distracted walking behaviours in Manhattan's most dangerous intersections. Issue 5 (25th March 2014) - Basch, Corey H; Ethan, Danna; Rajan, Sonali; Basch, Charles E
Abstract : Use of mobile devices has been cited as a distraction while driving, and more recently, among pedestrians crossing urban streets. In 2010, over half of New York City traffic fatalities were pedestrians. The aim of this study was to estimate the prevalence of distracted walking due to pedestrians' use of headphones, mobile phones, or both. Data were gathered by direct observations at the 10 intersections in Manhattan with the highest frequency of pedestrian–motor vehicle collisions. More than 1 in 4 of the >3500 pedestrians observed were distracted by mobile electronic devices while crossing during the 'walk' (28.8%) and 'don't walk' (26.3%) signals. Poisson regression analyses established there was a significant difference in individuals talking on a mobile device during the 'walk' signal versus the 'don't walk' signal; however, no other significant differences in other distracted walking behaviours were observed. This study contributes to the emerging literature on distracted walking behaviour by pedestrians in busy urban areas and can help to inform pedestrian-focused safety efforts.